Decentralized electrochemical biosensors for biomedical applications: From lab to home - Pramod K. Kalambate; Vipin Kumar; Dhanjai (Next Nanotechnology)
Integrated electrochemical biosensors represent the new generation of sensing tools in the biomedical field, delivering compact-sized, portable, wearable, and implantable devices. Advances in sensor fabrication methods, scalable material synthesis, microelectronics, flexible electronics, and wireless communication have enabled the evolution of biosensing devices from traditional hospital-centric systems to home-centric solutions, suitable for use by non-experts to analyze early signs of diseases. Despite these advancements, key challenges remain, including scalability, material durability, power management, and seamless integration of biosensor components into user-friendly platforms. The translation of these technologies involves strategies to overcome these challenges, such as developing cost-effective manufacturing methods and optimizing device design for real-world applications. Furthermore, the integration of these devices with the Internet-of-Things (IoT), Internet-of-Medical-Things (IoMT), artificial intelligence (AI), and machine learning (ML) algorithms has demonstrated breakthrough technological solutions for healthcare management, disease prognosis, and patient care. However, potential risks such as data security vulnerabilities, privacy concerns, and regulatory challenges must be addressed to ensure safe and ethical deployment of these technologies. Herein, we provide an in-depth analysis of the evolution of conventional electrochemical biosensors into miniaturized, integrated devices, focusing on their potential for better healthcare management and highlighting associated technical, regulatory, and ethical challenges. We also highlight key aspects of 6th generation sensing technology. Additionally, the role of IoT and AI-assisted technologies is critically discussed, presenting both their transformative benefits and the risks they pose in the biomedical field.